Therapeutic Approaches in Youth Psychiatry: The Art of Balancing Between ‘Do not Harm’ and ‘Best Possible Care’: An Editorial - Ghalloub, Perla; Emmanuel, Nancy (International Journal of Clinical Research, 2022)
Adolescence is one of the most critical periods of an individual’s life where the bulk of neurological, biological, and social development occur. During this stage, adolescents are forced to get out of their comfort zones such as home or school, to experience true variability and independence in their new environments. While this transition may be easy for some, it can be very cumbersome for others leading to the emergence of maladaptive behaviors and the manifestation and intensification of underlying disorders.